PENGEMBANGAN PRODUK DAUN KELOR MELALUI FORTIFIKASI DALAM UPAYA PENANGANAN STUNTING - Selpina Embuai; Moomina Siauta (MOLUCCAS HEALTH JOURNAL, 2020)
ABSTRACTBackground: Stunting is a condition where toddlers whose height for age is below the standard. Toddlers who have low body weight based on age are caused by insufficient intake of nutrients in the long term. Stunting can have a negative impact on cognitive and motor development and increase the risk of overnutrition, non-communicable diseases and reduce productivity in adulthood. The prevalence of stunting in the world in under-fives in 2020 has decreased significantly by 22% (4). The results of the 2018 Basic Health Research (Riskesdas) show that the prevalence of stunting in children under five in Indonesia has decreased by 6.4% from 37.2% (in 2013) to 30.8%. Various efforts have been made by the government to prevent and overcome stunting. One of them is by using Moringa leaves. Moringa is called the most economical plant and contains very good nutritional value so that it can be used as an alternative in overcoming nutritional problems. In addition, the use of Moringa can be used as biscuits which of course can be used as additional food for toddlersPurpose: Describing evidence based (review of facts) in the form of a literature review on Moringa Leaf Product Development Through Nutrification in the Handling of StuntingMethod:The method used in this Literature review begins with selecting a topic, then determining keywords to search for journals using English and Indonesian through several databases, including Google Scholar, Ebscho, Pro Quest, and journal of nursing science. This search is limited to journals from 2011 to 2021. The English keywords used are â€œMoringa Leaves and Stuntingâ€. For Indonesian use the keywords "Leaves of Moringa, Stunting, Fortification".Results: This review resulted in the effectiveness of Moringa leaves through fortification for stunting prevention in toddlersConclusion: Moringa leaves have enormous benefits in meeting the nutritional adequacy rate for toddlers. Fortification is very useful and is recommended so that it can be carried out by all circles of society to prevent stunting in toddlersKeywords : Moringa Leaf, Fortification, Stunting, Toddler ABSTRAKÂ Latar Belakang:Stunting merupakan suatu kondisi dimana balita yang tinggi badan untuk usia berada dibawah standar. Balita yang memiliki berat badan rendah berdasarkan usia disebabkan oleh asupan zat gizi yang tidak mencukupi dalam jangka panjang. Stunting dapat berdampak negatif pada perkembangan kognitif, motorik dan meningkatkan risiko kelebihan gizi, penyakit tidak menular serta mengurangi produktivitas pada saat dewasa. Prevalensi stunting di dunia pada balita pada tahun 2020 mengalami penurunan yang cukup signifikan yaitu sebesar 22%. Hasil Riset Kesehatan Dasar (Riskesdas) 2018 menunjukkan prevalensi stunting pada balita di Indonesia mengalami penurunan sebesar 6.4% dari 37.2% (Tahun 2013) menjadi 30.8%. Berbagai upaya telah dilakukan oleh pemerintah guna mencegah dan mengatasi stunting. Salah satu diantaranya adalah dengan memanfaatkan daun kelor. Kelor disebut seb.agai tanaman paling ekonomis dan mengandung nilai gizi yang sangat baik sehingga dapat dijadikan sebagai alternatif dalam mengatasi permasalahan gizi. Selain itu, pemanfaatan kelor dapat dijadikan biskuit yang tentunya dapat dijadikan sebagai makanan tambahan untuk balita.Â Tujuan:Menggambarkan evidence based (telaah fakta) dalam bentuk literature review tentang Pengembangan Produk Daun Kelor Melalui Nutrifikasi Dalam Upaya Penanganan Stunting.Â Metode:Metode yang di gunakan dalam Literature review ini diawali dengan pemilihan topik, kemudian ditentukan keyword untuk pencarian jurnal menggunakan Bahasa Inggris dan Bahasa Indonesia melalui beberapa database antara lain Google Scholar, Ebscho, Pro Quest, dan journal of nursing science. Pencarian ini dibatasi untuk jurnalnya mulai tahun 2011 sampai dengan tahun 2021. Keyword Bahasa Inggris yang digunakan adalah â€œMoringa Leaves and Stuntingâ€. Untuk bahasa Indonesia menggunakan kata kunci â€œDaun Kelor, Stunting, FortifikasiÂ Hasil:Review ini menghasilkan efektivitas dari daun kelor melalui fortifikasi untuk pencegahan stunting pada balitaÂ Kesimpulan:Daun kelor memiliki manfaat yang sangat besar dalam memenuhi angka kecukupan gizi pada balita. Fortifikasi sangat bermanfaat dan dianjurkan agar dapat dilakukan oleh semua kalangan masyarakat guna mencegah stunting pada balitaÂ Kata Kunci : Daun Kelor, Fortifikasi, Stunting, Balita